The four Gospels and the Revelation - Bible. N.T. Gospels. English. Lattimore. 1979; Lattimore, Richmond Alexander, 1906-1984 (New York, NY Farrar, 1979)
Includes notes.
Keywords: Bible. N.T. Gospels -- translation; Bible. N.T. Revelation -- translation